Intégrer la dimension genre dans l’enseignement supérieur : transformation de pratiques au niveau individuel et institutionnel - Annick Rossier; Jessica Dehler; Bernadette Charlier; Hélène Füger (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Many higher education institutions have been developing equal opportunities programmes. In this text, the topic addresses gender as a dimension of teaching effectiveness. The project e-qual carried out at the University of Fribourg (Switzerland) involved several departments and received the support of the University’s Rector office. The project promotes teachers’ awareness of gender issues in order to improve the quality of education working both at individual and institutional level. Designing new gender-related modules for the university’s training programme Did@cTIC, and elaborating a self-evaluation questionnaire on gender issues in teaching are concrete elements implemented throughout the programme. At the institutional level, changes introduced have been accepted, recognized, and supported by the different departments involved in the project. Nevertheless extending gender issues in teaching for most of the academic staff requires further efforts.